Mildenhall : memories of mystery and misgivings - Ashbee, Paul
Half a century on, the principals in the Mildenhall affair are deceased. Paul Ashbee, senior prehistorian of East Anglia, has no direct evidence, but material recollections from near to the time. His account, drawing on those memories, notices aspects different to those which are stressed by Richard Hobbs (above), a researcher of a younger generation looking at the written record.